Biomonitoring of Toxic Effects of Pesticides in Occupationally Exposed Individuals - Muhammad Arshad; Maryam Siddiqa; Saddaf Rashid; Imran Hashmi; Muhammad Ali Awan; Muhammad Arif Ali (Elsevier, 2016)
Background: Workers in pesticide manufacturing industries are constantly exposed to pesticides. Genetic biomonitoring provides an early identification of potential cancer and genetic diseases in exposed populations. The objectives of this biomonitoring study were to assess DNA damage through comet assay in blood samples collected from industry workers and compare these results with those of classical analytical techniques used for complete blood count analysis. Methods: Samples from controls (n = 20) and exposed workers (n = 38) from an industrial area in Multan, Pakistan, were subjected to various tests. Malathion residues in blood samples were measured by gas chromatography. Results: The exposed workers who were employed in the pesticide manufacturing industry for a longer period (i.e., 13-25 years) had significantly higher DNA tail length (7.04 μm) than the controls (0.94 μm). Workers in the exposed group also had higher white blood cell and red blood cell counts, and lower levels of mean corpuscular hemoglobin (MCH), MCH concentration, and mean corpuscular volume in comparison with normal levels for these parameters. Malathion was not detected in the control group. However, in the exposed group, 72% of whole blood samples had malathion with a mean value of 0.14 mg/L (range 0.01-0.31 mg/L). Conclusion: We found a strong correlation (R2 = 0.91) between DNA damage in terms of tail length and malathion concentration in blood. Intensive efforts and trainings are thus required to build awareness about safety practices and to change industrial workers' attitude to prevent harmful environmental and anthropogenic effects.